2019
DOI: 10.1002/slct.201803725
|View full text |Cite
|
Sign up to set email alerts
|

Dual Activities of Nano Silver Embedded Reduced Graphene Oxide Using Clove Leaf Extracts: Hg2+ Sensing and Catalytic Degradation

Abstract: Silver nanoparticles embedded reduced graphene oxide (rGO−Ag) nanocomposites are synthesized by green technique using clove leaf aqueous extract as reducing agent. The surface plasmon resonance (SPR) peak of silver nanoparticles (Ag NPs) at 410 nm in rGO−Ag nanocomposites is analysed by UV–visible spectroscopy. The intensity of surface plasmon resonance (SPR) peak of Ag NPs in rGO−Ag nanocomposites is decreased with addition of Hg2+ ion at small interval of time. This is due to the occurrence of redox reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…The zeta potential measurement is carried out to find the surface charge and stability of colloidal particles . Figure ‐a and Figure ‐b show the zeta potential study of Au NPs, and Au/PVA nanocomposites respectively.…”
Section: Resultssupporting
confidence: 56%
“…The zeta potential measurement is carried out to find the surface charge and stability of colloidal particles . Figure ‐a and Figure ‐b show the zeta potential study of Au NPs, and Au/PVA nanocomposites respectively.…”
Section: Resultssupporting
confidence: 56%
“…At the same time, the material is also a ected by the printing speed and extrusion speed. e speed ratio can change the thickness of the material [20]. e following will reset the proportional relationship between the printing speed and the extrusion speed of the printer for composite materials, and select the appropriate printing accuracy [21].…”
Section: D Printingmentioning
confidence: 99%
“…First, the GO-AgNPs were characterized by Uv-vis ( Figure 7A ), and GO was introduced as a control. It was found that the Uv-vis spectrum of GO has an obvious absorption peak at 230 nm, representing the π→π* transition of the C-C bond in GO ( Sahu, et al, 2019 ). The Uv-vis spectra of GO-AgNPs have characteristic peaks at 230 and 410 nm, the former is the characteristic peak of GO, and the latter is the surface plasmon resonance peak of AgNPs.…”
Section: Resultsmentioning
confidence: 99%
“…Zeta potential is the potential generated by the distributed charges around the nanoparticle, and the Zeta potential of the nanoparticle is an vital indicator of its stability, and its numerical value directly shows the stability of the nanoparticle in colloidal suspension ( Sahu, et al, 2019 ). The GO-AgNPs were characterized by DLS and the Zeta potential of the GO-AgNPs was measured to be −16.8 mV (Figure 8F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation